If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 7 + -10x = 10 + 3x + 12 Reorder the terms: 7 + 8x + -10x = 10 + 3x + 12 Combine like terms: 8x + -10x = -2x 7 + -2x = 10 + 3x + 12 Reorder the terms: 7 + -2x = 10 + 12 + 3x Combine like terms: 10 + 12 = 22 7 + -2x = 22 + 3x Solving 7 + -2x = 22 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 7 + -2x + -3x = 22 + 3x + -3x Combine like terms: -2x + -3x = -5x 7 + -5x = 22 + 3x + -3x Combine like terms: 3x + -3x = 0 7 + -5x = 22 + 0 7 + -5x = 22 Add '-7' to each side of the equation. 7 + -7 + -5x = 22 + -7 Combine like terms: 7 + -7 = 0 0 + -5x = 22 + -7 -5x = 22 + -7 Combine like terms: 22 + -7 = 15 -5x = 15 Divide each side by '-5'. x = -3 Simplifying x = -3
| 8k-k-8= | | 1/3=13/x | | y=25(2x) | | y^2-9y+7y-63= | | 2x+5-7x=7-1(5x+2) | | 0.4x-0.5=0.3x+7 | | ln(x+6)-ln(3)=ln(16) | | (3t+4)t=0 | | -8x-6-x-3= | | y=4x^2-3x-10 | | y^2-5y-6y+30= | | 12=5-x-6x | | x^2-6x+2x-3=9x+27 | | Y=-2(X^4+2X^2)+8 | | 0.66666a+1=11 | | (k+3)+(k+k-11)+k=64 | | 4y=2(y-5)-5 | | 8b=216 | | 3(4x-3)=5-2x/4 | | 6w+9=18w-3w+81 | | -2V+r=2k | | X-12y=-62 | | 0.5=-0.6ln(x)+1 | | y-49=-2 | | 86-2x=6-10x | | 1/x^3=0 | | 0=x-4+3x | | 1/x^3 | | 2xy+3z+1=0 | | x-3-8x-6= | | 5x-2=13x-19 | | 5w^2-30w+40=0 |